Psikoedukasi Pendidikan Sek Guna Mencegah Kekerasan Seksual Pada Anak Tunawisma - Idha Isnaningrum; Novi Marliani (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The phenomenon of sexual violence against children is increasing, demanding serious attention in prevention efforts. Psychoeducation regarding sex education for children, especially homeless people, is important to equip them with the knowledge and skills to protect themselves. This program aims to provide information about types of sexual violence, signs, and how to protect yourself. The methods used include providing materials, motivation and mentoring, with a focus on an interactive and inclusive approach. Results showed increased children's knowledge about reproductive health and ability to identify dangerous situations. Support from parents and the community is crucial in creating a safe and supportive environment. It is hoped that this collaboration can reduce the risk of dangerous sexual behavior and increase collective awareness about the importance of early sex education.